Folate grafted thiolated chitosan enveloped nanoliposomes with enhanced oral bioavailability and anticancer activity of docetaxel. Issue 37 (9th September 2016) - Sohail, Muhammad Farhan; Javed, Ibrahim; Hussain, Syed Zajif; Sarwar, Shoaib; Akhtar, Sohail; Nadhman, Akhtar; Batool, Salma; Irfan Bukhari, Nadeem; Saleem, Rahman Shah Zaib; Hussain, Irshad; Shahnaz, Gul
Abstract : Folate grafted and thiolated chitosan coated nanoliposomes were evaluated to improve the oral absorption and targeted pharmacological activity of docetaxel. Abstract : Folate grafted and thiolated chitosan was synthesized and wrapped on the surface of mixed phosphatidylcholine based nanoliposomes (NLs) to improve the oral absorption and targeted pharmacological activity of anti-cancer drugs against breast cancer. In this study, a chitosan derived thiomer, having intrinsic properties of P-glycoprotein (P-gp) efflux pump inhibition, mucoadhesion and controlled drug release at a target site, was exploited to improve the performance of docetaxel (DTX) loaded NLs for better oral pharmacokinetics, targeted anti-cancer activity, liposomal stability and the physical characteristics of NLs. Thiomer enveloped nanoliposomes (ENLs) and bare nanoliposomes (NLs) were synthesized with the ingredient ratio pre-determined via Response Surface Methodology (RSM) plots by Design Expert® software. ENLs and NLs were thoroughly characterized for their surface chemistry, particle size, zeta potential, PDI, encapsulation efficiency, stability and release profile. ENLs were spherical in shape with a particle size of 328.5 ± 30 nm, a positive zeta potential of 18.81 ± 2.45 and a high encapsulation efficiency of 83% for DTX. Controlled release of DTX from formulations was observed for over 72 h for each formulation. The presence of thiol groups at the surface of the ENLs resulted in higher swelling and in situ gelling properties compared to the corresponding NLs. Furthermore, ENL/mucin mixtures showed a time dependent increase in viscosity for up to 12 h, leading to a 19.07-fold increased viscosity. Ex vivo permeation and P-glycoprotein inhibiting properties, studied in rat's small intestine, showed a 9.6-fold higher permeation and 13-fold enhancement of DTX in the presence of ENLs. In vitro cytotoxicity studies indicated that the ENLs can efficiently kill MD-MB-231 breast cancer cells with 200 fold lower IC50 values than DTX alone as a positive control. The pharmacokinetic study revealed that the ENLs significantly improved the oral bioavailability of DTX i.e. up to 13.6 fold as compared to an aqueous dispersion of DTX. Therefore, these enveloped hybrid nanoliposomes (ENLs) have the potential to be developed as useful nanocarriers for efficient oral delivery and breast cancer management using DTX.